Understanding Marek`s Disease Immunity: A Continuing Challenge - Schat, K.A. (International Journal of Poultry Science, 2003)
Immune responses to infection with Marek`s disease virus (MDV) have been studied intensively since the isolation of MDV in cell cultures and the development of the vaccines around 1970. More than 30 years later, the understanding of the importance of different components of the acquired and innate immune responses is still limited. Antibody responses are less important than cell-mediated immune (CMI) responses due to the cell-associated nature of MDV, although maternal antibodies can interfere with the efficacy of vaccines. The proteins that are detected by the maternal antibodies remain unknown. CMI responses can be directed against a number of glycoproteins as well as immediate early and early proteins, but the relative importance of the responses against individual proteins is unknown. Information concerning the CMI epitopes is still lacking. The importance of antiviral versus antitumor immunity has not been settled. Different types of innate immune responses to MDV (e.g., NK cells, NO, macrophages, interferon-Y ) have been described. Information on the nature of the target cells recognized by NK cells is lacking. Do NK cells recognize specific MDV proteins or is the down regulation of MHC class I antigens sufficient to activate the NK cells? NO can inhibit MDV replication in vitro and in vivo, but infection with very virulent + strains results in increased levels of NO. It is certainly feasible that excessive NO production can lead to pathology. Finally, the relationship between different mechanisms of genetic resistance and immune responses is still incompletely understood.